MENINGKATKAN PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK MELALUI PERMAINAN LARI SIMPAI DAN LOMPAT BALOK PADA SISWA KELAS V SEKOLAH DASAR NEGERI 06 PURWODADI GROBOGAN TAHUN AJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Power of Interest of Teaching of Long Jump with Leapfrog Style then apply â€œgameâ€ methodwhich develops training of basic movement introduction and apply simpai and box to reducescarcity of equipment of long jump. The case at this research is student of fifth grade at ElementarySchool 06 Purwodadi Grobogan Year 2012/2013. This research has goal to upgradelong jump with lep frog style learning trough simpai run game and leap box game for student.This research applied class action method (PTK). I cycle on meeting and cycle II performedone time encounter . Research subject is a class V SD State 06 Purwodadi , Purwodadi Sub-district, Grobogan . Instruments data acquisition obtained from observations at the time oflearning , tests show student work and a written test .Based on the cycle I did not meet the Ministry of Health that is 42.86 % ( 18 students ) , cycleII that is 9,52 % ( 4 students ) . As a result I learned to cycle to meet the Ministry of Health of57.14 % ( 24 students ) and in cycle II increased to 90.48 % ( 38 students ) of thel 42 students.Based research result that the application to play the long jump squat style run game approachand jump collar beams can improve learning outcomes in the long jump squat style of fifthgrade at State Elementary School 06 Purwodadi and hoped for Teacher to apply this game.